The European Association for the Study of Obesity (EASO) Endorses the Milan Charter on Urban Obesity - Michele O. Carruba; Luca Busetto; Sheree Bryant; Antonio Caretto; Nathalie J. Farpour-Lambert; Giuseppe Fatati; Diego Foschi; Francesco Giorgino; Jason C.G. Halford; Andrea Lenzi; Giuseppe Malfi; Grace O'Malley; et al. (Obesity Facts, 2021)
The Milan Charter on Urban Obesity highlights the challenges of urban environments as a battleground for human health, as cities are often organized to subvert public health goals, and promote rather than prevent the development of obesity and consequent non-communicable diseases. The Charter articulates ten principles which detail actions and strategies through which general practitioners, diverse medical specialists, related healthcare professionals, administrators and healthcare practice managers, policy actors – within health systems and at a national level – along with experts across disciplines, and citizens, can work in cooperation to meet this challenge and improve public health. The Charter urges the adoption of decisions that deliver the following: (i) policies which enable our cities to become healthier and less obesogenic, more supportive of well-being and less health-disruptive in general, and (ii) policies that fully support primary prevention strategies, that address social stigma, and that ensure fair access to treatment for people living with obesity. The Milan Charter on Urban Obesity aims to raise awareness of our shared responsibility for the health of all citizens, and focuses on addressing the health of people living with obesity – not only as a challenge in its own right, but a gateway to other major non-communicable diseases, including cardiovascular diseases, type 2 diabetes, and some cancers.